Study of Different Acid Doped Polyaniline Nanostructures and Their Electrical Conductance Properties (Journal of Scientific Research, 2022)
The different acid doped polyaniline (PANI) materials were prepared in situ using mineral acids like HCl, H2SO4, HNO3 and HClO4 of different concentrations in presence of 0.2 M aniline solution and 0.25 M ammonium persulfate as oxidising agent by the chemical oxidation method. The synthesized materials were studied for their physico-chemical characterizations like XRD, IR and SEM. IR studies revealed the formation of emeraldine salt in all the acid doped PANI samples. XRD of samples exhibited the partly crystalline structure of which HClO4 doped showed good crystallinity over other samples. SEM images displayed the formation of nanorods like structural agglomerates. The effect of acid dopants on their electrical conductivity was investigated by using the four probe set up technique. It was found that HClO4 doped PANI exhibited good electrical conductivity over the other acid doped samples whereas the lowest electrical conductivity was recorded for HNO3 doped PANI samples. The electrical conductivity of 1 M HClO4 doped PANI was the highest i.e.  9.1 S cm-1 among all PANI samples.